2019
DOI: 10.1007/s42452-019-0638-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different surface topographies of titanium implants on bacterial biofilm: a systematic review

Abstract: To compare the different surface topographies of titanium implants used in dentistry against the formation of bacterial biofilm. To identify relevant studies, the electronic databases PubMed, Science Direct and Springer Link were searched from inception until January 2019. A total of 38 studies were selected for the systematic review (n = 38). The most commonly used titanium surfaces were machined titanium (16.3%), sandblasted, large-grit, acid-etched titanium (10.9%), untreated or pure titanium (10.9%), polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Low contamination was shown when Sa was less than 0.6, whereas an increase in the Sa value results in a saturation process with a higher presence of bacteria. This agrees with a review of Dhaliwal et al, which [23] showed that the topographies have a beneficial effect on the bacterial colonization [24,25]. Bacterial colonization is reduced in machined titanium implants than in zirconia and other sandblasted and acid-etched surfaces [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…Low contamination was shown when Sa was less than 0.6, whereas an increase in the Sa value results in a saturation process with a higher presence of bacteria. This agrees with a review of Dhaliwal et al, which [23] showed that the topographies have a beneficial effect on the bacterial colonization [24,25]. Bacterial colonization is reduced in machined titanium implants than in zirconia and other sandblasted and acid-etched surfaces [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have established several premises that predict increased or decreased bacterial adhesion to particular substrates. However, the results of many of these studies are controversial. , Several works have studied the effect of the topography of substrates prepared by lithography, which produces regular patterns at the micro- and nanoscales, such as grooves, pits, pillars, and honeycombs, among others. Surfaces with microscale patterns have increased bacterial adhesion, which is attributed to more contact surface and less shear force under a moving fluid . These studies have shown that bacteria tend to bind preferentially to patterns in the micrometer range rather than to smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a growing amount of evidence [5,6] suggests that the implant surface topography and chemistry has great influence on the osseointegration process by affecting protein signalling and cell migration or differentiation. Bone-implant contact area, mechanical interlocking and stress distribution are recognisably better in surfaces with a certain degree of roughness in comparison to smooth ones, favouring osteoblast-like cell colonisation [7].…”
Section: Introductionmentioning
confidence: 99%